Challenges of Arabic Language Learning in the 21st Century: A Pedagogical, Digital, and Cultural Study - Muh. Zakki Amrulloh; Sofan Sulong; Muhammad Suhaimi Haengyama; Fitria Rahmatun Nisa (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mmojokerto, 2026)
Arabic language learning in the 21st century is increasingly important to study because pedagogical, digital, and cultural changes demand a more communicative, adaptive, and relevant learning orientation to the needs of modern education. This article aims to identify the main challenges of Arabic language learning, explain the interrelationships among pedagogical, digital, and cultural challenges, and formulate directions for transforming 21st-century Arabic language learning. This research employs a qualitative approach grounded in a conceptual literature review. Data was collected through a search of academic literature from Google Scholar, DOAJ, Garuda, and Scopus or Sinta-indexed articles, with relevant inclusion and exclusion criteria. Analysis was conducted thematically-conceptually to find patterns, relationships, and synthesis of ideas from various sources. The results show that pedagogical challenges include the dominance of grammatical-memorization approaches, limitations of active learning, and teacher competence; digital challenges include technological literacy, infrastructure, and AI integration; while cultural challenges relate to learners' perceptions, identity, and social context. This article concludes that the transformation of Arabic language learning needs to be directed towards a communicative-integrative approach, appropriate technology-based solutions, and cultural sensitivity. Further research is suggested to test these conceptual findings through empirical studies in various educational contexts.